Histological study of pars tuberalis of the pituitary gland in local male buffaloes ″Bubalus bubalis: Malallah, H. B ,Hussin, A. M. - H. B, Malallah (The Iraqi Journal of Veterinary Medicine, 2010)
This study was carried out on the pituitary gland of eight male buffaloes 3-5 years old, examined under light microscope. The histological results revealed that the pars tuberalis contained four types of cells, not similar to any other cell types of the pars distalis. This finding and the location of the pars tuberalis at the gate of pars distalis which control the blood circulation give the pars tuberalis a special functional importance.